A Preliminary Study on Antimicrobial Susceptibility of Staphylococcus spp. and Enterococcus spp. Grown on Mannitol Salt Agar in European Wild Boar (Sus scrofa) Hunted in Campania Region—Italy - Francesca Paola Nocera; Gianmarco Ferrara; Emanuela Scandura; Monica Ambrosio; Filomena Fiorito; Luisa De Martino (Animals, 2021)
The importance of wild boar lies in its role as a bioindicator for the control of numerous zoonotic and non-zoonotic diseases, including antibiotic resistance. Mannitol Salt Agar (MSA) is a selective medium used for isolation, enumeration, and differentiation of pathogenic staphylococci. Other genera such as Enterococcus spp. are also salt tolerant and able to grow on MSA. The present study focused on the identification, by matrix assisted laser desorption/ionization-time of flight mass spectrometry (MALDI-TOF-MS), of bacteria grown on MSA isolated from the nasal cavities of 50 healthy wild boars hunted in Campania Region (southern Italy) in the year 2019. In addition, the antimicrobial resistance phenotype of the isolated strains was determined by disk diffusion method. Among genus Staphylococcus, coagulase-negative Staphylococcus (CoNS) were the most common isolated species, with Staphylococcus xylosus as the most prevalent species (33.3%). Furthermore, Enterococcus spp. strains were isolated, and Enterococcus faecalis was the species showing the highest frequency of isolation (93.8%). For staphylococci, high levels of resistance to oxacillin (93.3%) were recorded. Differently, they exhibited low frequencies of resistance to tested non-β-lactams antibiotics. Among enterococci, the highest resistances were observed for penicillin (93.7%), followed by ampicillin (75%), and ciprofloxacin (68.7%). Interestingly, 43.7% of the isolated strains were vancomycin-resistant. In conclusion, this study reports the phenotypic antibiotic resistance profiles of Staphylococcus spp. and Enterococcus spp. strains isolated from nasal cavities of wild boars hunted in Campania Region, highlighting that these wild animals are carriers of antibiotic resistant bacteria.